Pengaruh Penggunaan Teknik Role Playing dalam Bimbingan Kelompok Terhadap Komunikasi Interpersonal Pada Peserta Didik - Himatul Safitri; Moesarofah Moesarofah (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2020)
Interpersonal communication is a part of developing student development, because through interpersonal communication learners can interact with others, but only a few learners have good interpersonal communication skills. Students with low interpersonal communication problems tend to be passive in their environment, thereby inhibiting learners ' progress. The study aims to test the influence of the use of role playing techniques in group guidance on interpersonal communication in high school learners. This research uses a quantitative approach with the research method of one group pre-Test post-Test design. Data collection methods use interpersonal communication scales, interviews, and observations. The study used group guidance services with role playing techniques given to 10 students of class X SMA Z in Surabaya with low interval categories. The Group guidance service was conducted six times the meeting with a time allocation of 40 minutes. The analysis of the data used is Wilcoxon's test with a significance limit of 0.05. The results of the analysis obtained amounted to 0.005 ? 0.05, so the findings of this research gained a significant influence in the use of Group guidance services with role playing techniques on interpersonal communication to students of class X in high School.